Penerapan Metode Demonstrasi dalam Sistem Pembelajaran Daring Mata Pelajaran Fiqih Materi Adzan dan Iqomah Kelas II MI Ma’arif Pengempon Tahun 2020/2021 - Agus Nur Soleh (LPPM IAINU Kebumen, 2020)
Implementation Method Demonstrasi Dalam Sistem Pembelajaran Daring Mata Pelajaran Fiqih Materi Adzan dan Iqomah Kelas II Mi Ma’arif Pengempon Tahun 2020/2021” The focus of research in this thesis is 1. how to apply the demonstration method in the learning system of fiqh, adhan and iqomah class 2 mi ma'arif pengempon. 2. what are the advantages and disadvantages of using demonstration methods in online learning systems The type of research used is qualitative research. In this research, the data collection techniques used were observation, interview and documentation, The results of the study show that 1. the implementation of fiqh learning with the adhan and iqomah material using the online learning system demonstration method. There are several steps taken by the teacher, including making RPP before implementing the learning. 2 in the learning process, the teacher carries out several stages consisting of preliminary, core and closing activities. The advantages and disadvantages of implementing fiqh learning with online system demonstration methods on the adzan and iqomah material.shortcomings in the learning process Application of the method of demonstration of the network system, including learning ineffective networks, sometimes errors, the quota costs are expensive because everything uses the internet network